2014
DOI: 10.1590/s0100-736x2014001300009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, hematological, total plasma protein and fibrinogen parameters of magellanic penguins ( Spheniscus magellanicus ) pre- and post-rehabilitation

Abstract: The aims of this study were to determine the hematologic, total plasma protein (TPP) and fibrinogen profiles of young and adult magellanic penguins in PROAMAR and CETAS-SC, relating these results with the state of health and survival possibility of the animals. In Paraná 14 animals were evaluated in pre and eight in post-rehabilitation and 29 animals were evaluated in Santa Catarina after rehabilitation. Before rehabilitation, all animals showed weakness. In hematological exams of these animals, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Despite the association of fibrinogen with inflammatory lesions, due to the lack of accurate fibrinogen detection methods, increases in fibrinogen in Gentoo penguins with an inflammatory lesion named bumblefoot were undetected . In addition, no increases were observed in recently captured Humboldt penguins and in Magellanic penguins, which were in rehabilitation facilities. , This calls for the development of epitope-specific detection methods, such as the generation of antibodies that accurately recognize fibrinogen across multiple species (Figure ). The area highlighted in red indicates a potential region that is conserved between multiple species and can be targeted for the development of antibody detection methods.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the association of fibrinogen with inflammatory lesions, due to the lack of accurate fibrinogen detection methods, increases in fibrinogen in Gentoo penguins with an inflammatory lesion named bumblefoot were undetected . In addition, no increases were observed in recently captured Humboldt penguins and in Magellanic penguins, which were in rehabilitation facilities. , This calls for the development of epitope-specific detection methods, such as the generation of antibodies that accurately recognize fibrinogen across multiple species (Figure ). The area highlighted in red indicates a potential region that is conserved between multiple species and can be targeted for the development of antibody detection methods.…”
Section: Resultsmentioning
confidence: 99%
“…Leukogram findings included a heterophil concentration within normal limits, a mildly increased heterophil-lymphocyte ratio, and mild hyperfibrinogenemia (400 mg/dL; reference interval, 180–260 mg/dL). 2 Plasma biochemistry panel findings included elevated aspartate aminotransferase (AST; 1568 IU/L; reference range, 128–308 IU/L) 1 and creatine kinase (CK; 3989 IU/L; reference range, 147–691 IU/L). 1 Trace element analyses demonstrated an elevated iron concentration at 44 ppm (reference interval, <25 ppm) that was most likely secondary to ongoing disease rather than toxicity.…”
Section: Clinical Reportmentioning
confidence: 99%
“…Therefore, it is essential to acquire normal hematology and serum biochemistry intervals for each species in both the wild and captivity. Several studies have reported the normal blood values of wild Little ( Eudyptula minor ), Rockhopper ( Eudyptes chrysocome ), Magellanic ( Spheniscus magellanicus ), Gentoo ( Pygoscelis papua ), Adélie ( P. adeliae ), Chinstrap ( P. antarcticus ), Humboldt ( S. humboldti ), and Galápagos ( S. mendiculus ) penguins (Aguilera, Moreno, & Ferrer, ; Coraiola, Kolesnikovas, Krul, Mangini, & Locatelli‐Dittrich, ; Hawkey, Horsley, & Keymer, ; Karesh et al, ; Nicol, Melrose, & Stahel, ; Smith et al, ; Travis et al, ), as well as captive Gentoo, Humboldt, African ( S. demersus ), and Magellanic penguins (Bechert et al, ; Campos et al, ; Hawkey, Samour, Henderson, & Hart, ; Mazzaro et al, ). The influence of species, age, and gender on blood parameters has also been evaluated.…”
Section: Introductionmentioning
confidence: 99%